2006
DOI: 10.2176/nmc.46.92
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Hemangiopericytoma Manifesting as Massive Intracranial Hemorrhage-Two Case Reports-

Abstract: Meningeal hemangiopericytoma is rare, and only seven cases have manifested as intracranial hemorrhage. We treated two patients with meningeal hemangiopericytoma manifesting as life-threatening massive intracerebral hemorrhage. Case 1: A 66-year-old woman presented with consciousness disturbance and left hemiparesis. Computed tomography showed a mass lesion in the right frontal parasagittal region and massive hematoma in the brain tissue at the medial border of the lesion. Immediate evacuation of the hematoma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…It accounts for only 1% of all primary CNS tumors (5). Intracranial HPC was previously believed to originate from the meninges; thus, it was considered a subtype of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for only 1% of all primary CNS tumors (5). Intracranial HPC was previously believed to originate from the meninges; thus, it was considered a subtype of meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, among cases of sudden unexpected death arising from primary brain tumor, colloid cysts of the third ventricle are the most frequent, followed by gliomas, ependymomas, and meningiomas [ 6 – 10 ]. However, only three cases of sudden unexpected death arising from intracranial hemangiopericytoma have been reported, including the present case ( Table 1 ) [ 4 , 6 , 11 ].…”
Section: Discussionmentioning
confidence: 98%
“…Mena et al reported that 22 of 94 intracranial hemangiopericytoma cases (23.4%) exhibited intratumoral hemorrhage [ 13 ]. Cervoni et al summarized and reviewed nine cases of meningeal hemangiopericytoma associated with subarachnoid [ 5 ], subdural [ 3 , 14 ], intratumoral [ 12 ], and intracerebral hemorrhage [ 11 , 15 , 16 ]. All cases involved supratentorial lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Bleed in tumor is very rare. Till date, only 8 cases of hemangiopericytoma have been reported that presented with intracranial bleed . These have presented in different forms as intraparenchymal, subdural or subarachnoid hemorrhage and a combination of these .…”
Section: Discussionmentioning
confidence: 99%
“…Though pre‐operative embolization has been recommended for these vascular tumors, it is not possible in an emergency setting due to raised intracranial pressure. A staged approach can also be performed wherein evacuation of hematoma is done in first setting and tumor excised later after the patient's neurological condition improves .…”
Section: Discussionmentioning
confidence: 99%